2021
DOI: 10.1371/journal.pntd.0009951
|View full text |Cite
|
Sign up to set email alerts
|

Chalcones identify cTXNPx as a potential antileishmanial drug target

Abstract: With current drug treatments failing due to toxicity, low efficacy and resistance; leishmaniasis is a major global health challenge that desperately needs new validated drug targets. Inspired by activity of the natural chalcone 2’,6’-dihydroxy-4’-methoxychalcone (DMC), the nitro-analogue, 3-nitro-2’,4’,6’- trimethoxychalcone (NAT22, 1c) was identified as potent broad spectrum antileishmanial drug lead. Structural modification provided an alkyne containing chemical probe that labelled a protein within the paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Furthermore, it is in medicinal chemistry that chalcones are rightfully considered to have a privileged structure [ 5 ], since the chalcone core is present in a variety of important bioactive compounds with a broad spectrum of pharmacological activities, such as antimalarial, antibacterial, anticancer, anti-inflammatory, antiplasmodial, antioxidant, antifungal, antitubercular and antiviral agents [ 5 , 6 ]. Furthermore, recent reports have further indicated that chalcone derivatives ( Figure 1 ) may also be a promising pharmacophoric group against diseases caused by protozoa, including leishmaniasis [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is in medicinal chemistry that chalcones are rightfully considered to have a privileged structure [ 5 ], since the chalcone core is present in a variety of important bioactive compounds with a broad spectrum of pharmacological activities, such as antimalarial, antibacterial, anticancer, anti-inflammatory, antiplasmodial, antioxidant, antifungal, antitubercular and antiviral agents [ 5 , 6 ]. Furthermore, recent reports have further indicated that chalcone derivatives ( Figure 1 ) may also be a promising pharmacophoric group against diseases caused by protozoa, including leishmaniasis [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antileishmanial activity of chalcones has been largely investigated through phenotypic assays. The mode of action of synthetic and natural chalcones has not been elucidated yet, even though some targets, such as the arginase enzyme or enzymes involved in the trypanothione metabolic pathways [14][15][16], have been postulated. In addition, licochalcone A has been shown to alter the ultrastructure of the mitochondria and to inhibit the activity of fumarate reductase in the respiratory chain of L. major promastigote [17,18] Molecules 2022, 26…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the natural products’ mode of action, oxidative stress figures as one of the most recurrent processes directly involved in their biological effect. The increase in ROS production as a result of chalcones treatment was already reported in trypanosomatids [ 22 , 23 , 24 , 40 ]. Here, the compound NaF at IC 50 /24 h concentration induced a remarkable increase in ROS levels in P. serpens promastigotes, similar to that previously observed in T. cru z i and L. amazonensis treated with other plant secondary metabolites, sesquiterpenoids and flavonoids , respectively [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 66%